Unearthing prehistoric diets: First evidence of horse meat consumption in Early Bronze Age Sicily - Davide Tanasi; Roberto Micciché; Robert H. Tykot; Luis Busetti; Pierluigi Barbieri; Gianpiero Di Maida; Viviana Ardesia; Alessandro Miani; Elia Marin; Enrico Greco (PLoS ONE, 2025)
This paper presents the earliest documented evidence for the presence and consumption of horse meat in Early Bronze Age Sicily, significantly revising previous understandings of equid use on the island. Multidisciplinary analyses involving proteomics and lipidomics were performed on ceramic vessels from the Castelluccian settlement at Polizzello Mountain (Caltanissetta), revealing residues consistent with equine-derived substances. Proteomic data unequivocally identified equine serum albumin in multiple pottery fragments, demonstrating active consumption or processing of horse-derived substances within a ceremonial or dietary context. Lipid residues further supported this interpretation, indicating the presence of animal fats and vegetable-derived substances within the pottery. These findings substantially alter existing models of horse domestication, utilization, and dietary practices in prehistoric Sicily, suggesting a far earlier and more complex human-equid relationship. Furthermore, the integration of biomolecular data enhances our understanding of intercultural interactions, ritual behaviors, and economic strategies in the central Mediterranean during the third millennium BCE.